2019
DOI: 10.1186/s12879-019-3905-7
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of leptospirosis with predominant cardiac involvement: a case series

Abstract: BackgroundSevere leptospirosis is known to cause multi organ dysfunction including cardiac involvement. In the clinical setting with limited resources, high degree of suspicion is needed to diagnose cardiac involvement including myocarditis. Although myocarditis is not reported as a common complication due to lack of diagnostic facilities, there are evidence to support myocarditis is more prevalent in post mortem studies of patients died due to leptospirosis. We present a case series of severe leptospirosis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…Though the increasing awareness is contributing to increase detection, the large number of patients reported in this study with SPHS could not be attributed totally to increased awareness. Several recent reports from Sri Lanka showed that the different outbreaks of leptospirosis are associated with different clinical presentations such as pancreatitis [28] and cardiac involvement [29]. Further, regional differences of leptospirosis in Sri Lanka are partly explained with infecting Leptospira [30].…”
Section: Discussionmentioning
confidence: 99%
“…Though the increasing awareness is contributing to increase detection, the large number of patients reported in this study with SPHS could not be attributed totally to increased awareness. Several recent reports from Sri Lanka showed that the different outbreaks of leptospirosis are associated with different clinical presentations such as pancreatitis [28] and cardiac involvement [29]. Further, regional differences of leptospirosis in Sri Lanka are partly explained with infecting Leptospira [30].…”
Section: Discussionmentioning
confidence: 99%
“…Endocardial inflammation with vasculitic changes has been reported as one of the pathogenic mechanisms of disease in a report of the pathological examination of hearts from patients who died from leptospirosis. Due to associated multiorgan involvement, the cardiac manifestations may possibly be underdiagnosed [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leptospira antigens were easily demonstrated in myocytes, interstitium and endothelial cells. From a clinical point of view, myocarditis has important consequences in severe leptospirosis 27,28 . It seems that the cardiac muscle was involved in the course of septicemia, through hematogenous dissemination 29,30 .…”
Section: Discussionmentioning
confidence: 99%